Performance issues of bandwidth reservations for grid computing - Burchard, L. -O.; Heiss, H. -U.; De Rose, C. A. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
In general, two types of resource reservations in computer networks can be distinguished: immediate reservations which are made in a just-in-time manner and advance reservations which allow to reserve resources a long time before they are actually used. Advance reservations are especially useful for grid computing but also for a variety of other applications that require network quality-of-service, such as content distribution networks or even mobile clients, which need advance reservation to support handovers for streaming video. With the emerged MPLS standard, explicit routing can be implemented also in IP networks, thus overcoming the unpredictable routing behavior which so far prevented the implementation of advance reservation services. The impact of such advance reservation mechanisms on the performance of the network with respect to the amount of admitted requests and the allocated bandwidth has so far not been examined in detail. We show that advance reservations can lead to a reduced performance of the network with respect to both metrics. The analysis of the reasons shows a fragmentation of the network resources. In advance reservation environments, additional new services can be defined such as malleable reservations and can lead to an increased performance of the network. Four strategies for scheduling malleable reservations are presented and compared. The results of the comparisons show that some strategies increase the resource fragmentation and are therefore unsuitable in the considered environment while others lead to a significantly better performance of the network. Besides discussing the performance issue, the software architecture of a management system for advance reservations is presented.